THE STRATEGY OF POLITENESS IN EXPRESSIVE SPEECH ACT OF SHINZO ABE’S RESIGNATION SPEECH - Diana Kartika; M. Aziz (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
Japan is a country led by a Prime Minister. Japanese history proves that Shinzo Abe was the longest-serving Prime Minister. However, right at the time of Covid-19 and still having one year in office, Shinzo Abe has resigned. This study used a qualitative method and analyzed it descriptively. The data were obtained by a library research system which was sourced from the transcript of Shinzo Abe's opening resign speech and grouped in expressive speech act according to Searle’s theory (1979) and analyzed by the politeness strategies according to Nomura Asaki and Koike Seiji’s theory and based on verb-syntactical. This research concluded that Shinzo Abe used a politeness strategy in the form of kenjougo and teineigo with four expressions of thanks/gratitude, one expression of condolence, and one expression of pardon/apology. The speech was raised by Shinzo Abe with a politeness strategy of lowering his speech and respecting the feelings of the Japanese people.